Strategi Gamifikasi terhadap Loyalitas Pelanggan Fairy Nails - Tiris Sudrartono; Femmy Indah Pertiwi (Universitas Batanghari Jambi, 2026)
This study aims to analyze the effect of implementing a gamification strategy on Fairy Nails' customer loyalty in 2023-2024. The study used a quantitative descriptive method. Quantitative data in the form of number of customers, frequency of visits, repeat purchase rate (RPR) per quarter, and monthly sales data before and after the gamification program adjustments were obtained from internal documentation and processed using descriptive analysis in the form of percentage calculations and before and after calculations. The results show that Fairy Nails implements gamification through a loyalty card-based points collection and reward exchange system. Empirically, the implementation of gamification has not been able to increase loyalty sustainably; RPR only increased in the first quarter of 2024 (27%) and decreased again in the second-third quarter of 2024 (19%). This study recommends simplifying the points system, increasing the reward value, digitizing point recording, and developing challenges and referral programs that are more suited to customer characteristics to increase customer engagement and loyalty.